2011
DOI: 10.1371/journal.pone.0020878
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Changes in Phospho-MAP/Tau Epitopes during Neuronal Stress: Cofilin-Actin Rods Primarily Recruit Microtubule Binding Domain Epitopes

Abstract: Abnormal mitochondrial function is a widely reported contributor to neurodegenerative disease including Alzheimer's disease (AD), however, a mechanistic link between mitochondrial dysfunction and the initiation of neuropathology remains elusive. In AD, one of the earliest hallmark pathologies is neuropil threads comprising accumulated hyperphosphorylated microtubule-associated protein (MAP) tau in neurites. Rod-like aggregates of actin and its associated protein cofilin (AC rods) also occur in AD. Using a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 67 publications
6
25
0
Order By: Relevance
“…AT100 staining showed the previously described, unspecific nuclear localization [32]. Biochemical analysis did not reveal an age-dependent increase of total, insoluble or phosphorylated tau (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…AT100 staining showed the previously described, unspecific nuclear localization [32]. Biochemical analysis did not reveal an age-dependent increase of total, insoluble or phosphorylated tau (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…32 Studies using mice later demonstrated that cofilin rods might influence microtubule organization and intracellular trafficking by affecting the redistribution and phosphorylation of microtubule associated protein. 33,34 Together, these studies strongly support the hypothesis that cofilin may be involved in the regulation of tubulin dynamics and stability, and thereby platelet production in MKs.…”
Section: Discussionsupporting
confidence: 67%
“…3; [8]), and the loss of neuronal integrity may be affecting total and phosphorylated tau levels in the neuron. A recent study [29] demonstrated that after antimycin A treatment, the presence of Ser 262/356 ‐tau increases, while total tau and tau phosphorylated at Ser 396/404 decreases. This was shown to be a result of the specific recruitment of Ser 262/356 ‐tau to actin‐cofilin rods.…”
Section: Discussionmentioning
confidence: 98%